The Use of Manipulative Language by Esther in the Film "Orphan" by David Leslie Jhonson: Manipulative Language, Linguistic Manipulation, Orphan Film by David Leslie Jhonson (2009), Power and Control, Emotional Framing - Rustandi, Encep (ELATICS JOURNAL, 2025)
This research examines the use of manipulative language in the film Orphan by David Leslie Jhonson a story by Alex Mace (2009), focusing on the character Esther who, despite her innocent appearance, uses sophisticated linguistic strategies to influence, deceive, and control others to achieve her hidden goals, by employing emotional framing, exploiting sympathy, and combining lies with incomplete thrust, Esther successfully manipulates how people around her perceive Esther. This research will analyse these manipulation tactics from psychological and linguistic perspectives, emphasizing the power and control dynamics demonstrated through Esther's character in this Orphan film. Additionally, this research compares the manipulative language in the film with its real-world applications in interpersonal relationships involving varying degrees of power. The research focuses on Esther’s conversation with other characters to show how she uses language to manipulate, which heightens narrative tension, influences audience perception, and reflects human behaviour.